Toleransi dalam Teologi Agama-Agama: Studi Komparatif - Mawardi Mawardi (Raudhatun Najah Publisher, 2024)
This article aims to explore the concept of tolerance in the theology of religions, focusing on how the values of tolerance can be applied in interreligious relations to create social harmony. This study employs a qualitative approach using descriptive analysis and library research methods, utilizing primary and secondary sources such as sacred texts, theological literature, and previous studies on tolerance in religious contexts. The findings reveal that tolerance is a key element in many religious theologies, emphasizing respect for differences in belief and the necessity of interfaith dialogue. These findings highlight the importance of an inclusive and open theological approach in strengthening interreligious relations, while also challenging exclusivist attitudes that often trigger conflicts. Therefore, this research offers a significant contribution to the discourse on tolerance and the role of religion in building a peaceful and inclusive society.